Implication of Thrombus Marker (D-Dimer) Levels in Preeclamptic Pregnant Women During the Third Trimester - Edebiri O.E; Akpe C. I.; Adewole A.S.; Okike P.I.; Obiesi C. N; Ohiwerei W.O.; Orunta E.D. (The International Science of Health Journal, 2025)
Microvasculature fibrin deposition is implicated in preeclampsia. D-Dimer has emerged as a useful diagnostic tool for thrombotic conditions because its plasma concentration has a high negative implicative value for veinous thromboembolism. Forty (40) consenting pregnant women were recruited from St. Philomina Catholic Hospital, Edo State, Nigeria. These subjects consisted of  twenty (20) normotensive  and twenty (20) preeclamptic pregnant women in their  third trimester of pregnancy. Blood samples was spun in a bucket centrifuge at 2500 RPM (rounds per minute) for 10 minutes after which plasma was collected  and stored frozen in plain sample bottles and was analyzed for thrombus marker (D- Dimer)  levels  by fluorescence immunoassay  method.